EFFECTIVENESS AND SAFETY OF VELAGLUCERASE ALFA IN TREATMENT OF GAUCHER DISEASE TYPE 1 (ACCORDING TO INTERNATIONAL STUDIES) - O. S. Gundobina; G. B. Movsisyan; E. V. Komarova; L. S. Namazova-Baranova (Педиатрическая фармакология)
The article is dedicated to modern approaches to treatment of Gaucher’s disease. The authors list the primary aspects of the disease and present data on the origin and introduction of pathogenetic enzyme replacement therapy to clinical practice. Review of international clinical studies demonstrates high effectiveness and safety of long-term enzyme replacement therapy with velaglucerase alfa in patients with confirmed type I Gaucher’s disease.